Determining appropriate harvesting time for orange (high vitamin A) maize based on consumer preferences in Western Africa - CGIAR Research Program on Maize (2021)
Nutritionists, food scientists, and maize breeders could use the information from this study to select the best maize genotypes at the appropriate harvesting period suitable for the production of the preferred maize-based products of consumers.